Local food innovation for food security in west timor during social restrictions - Taena, Werenfridus; Nino, Jefrianus; Yustiningsih, Maria; Sila, Vinsensia Ulia Rita; Binsasi, Yeremias (Asian Journal of Agriculture and Rural Development, 2025)
Food security during social restrictions is crucial, making the strengthening of local food systems essential in such situations. The study aims to (i) analyze the influence of food processing technology innovation, local food management, and the quality of local food on food security in West Timor during social restrictions, and (ii) identify strategic priorities for achieving food security in West Timor. The research was conducted on Timor Island, particularly in North Central Timor Regency, with a sample of 75 respondents distributed across four sub-districts. The analysis employed logistic regression and the Analytical Hierarchy Process (AHP). The logistic analysis revealed that innovation in local food management significantly influenced food security (α = 5%) with an odds ratio of 18.119, whereas innovation in local food processing technology (odds ratio = 1.429) and the quality of local food (odds ratio = 1.593) were not statistically significant. Further analysis using AHP identified the strategic priorities for achieving food security, which included: technology transfer procedures (32.20%), upstream and downstream integration of local food—including production, preservation, processing, packaging, marketing, and consumption (31.90%), regulation of local food nutritional standards (21.90%), and management of local food stocks (14.10%). Based on these findings, a comprehensive roadmap is necessary to effectively achieve food security in the region.